Self Harm and Suicide in Adolescents - M. Fardi Anugrah; Khaula Karima; Ni Made Sri Padma Puspita; Nurul Aulia Binti Amir; Agustine Mahardika (Jurnal Biologi Tropis, 2023)
Self harm is also called Non-Suicidal Self-Injury (NSSI). NSSI is defined as intentional self-injurious behavior to cause minor bodily harm without suicidal intent. Self-harm is strongly associated with suicidal thoughts and approximately 27-30% of adolescents with NSSI have reported suicide attempts. Based on the explanation above, the author is interested in discussing self-harm and suicide to explore the definition and management of self-harm and suicidal behavior in adolescents. In writing this literature review, we used a literature study method from various references and focused on discussions about self-harm and suicide. The search engines used were PubMed, ProQuest, and Google Scholar with the keywords "Self harm and suicide", "Epidemiology", "Diagnosis", and "Management". Overall, there were 30 articles used as references for preparing the literature review. The results of the investigation showed that self-harm and suicide are mental problems that often occur in teenagers and therefore require appropriate management using non-pharmacological and pharmacological medical approaches.